1983
DOI: 10.1161/01.hyp.5.6_pt_3.v29
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen concentration in the cerebrospinal fluid in different experimental conditions in the rat.

Abstract: SUMMARY Angiotensinogen is the most important component of the renin-angiotensin system present in the cerebrospinal fluid (CSF) of the rat. Its physiological significance as well as its origin have not been clearly elucidated. In this experiment we have examined plasma renin activity (PRA) and plasma and CSF angiotensinogen concentration under the following experimental conditions in male rats of the Wistar strain: 1) adrenalectomy (Adx) 4 days prior to sample collection; controls were sham Adx animals; 2) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Activation of renin-angiotensin-adolesterone system (RAS) is critical for the pathogenesis of reno-hypertension [20,24]. In our 2k2c model, RAS activation was characterized by a significant increase in plasma Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of renin-angiotensin-adolesterone system (RAS) is critical for the pathogenesis of reno-hypertension [20,24]. In our 2k2c model, RAS activation was characterized by a significant increase in plasma Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant sources of AGT in the brain are astrocytes, which have been reported to constitutively secrete AGT into the extracellular and cerebrospinal fluids (9,35,40). In addition to the AGT-positive astrocytes that are found throughout the brain, AGT is also present in a limited population of neurons in regions of the brain dedicated to cardiovascular control (45).…”
mentioning
confidence: 99%
“…Plasma and CSF angiotensinogen levels were not influenced by furosemide injection, which showed a stimulatory effect on the renin-angiotensin system. Changes in plasma angiotensinogen due to salt restriction or water deprivation remain controversial (Ruiz et al, 1983, Schelling et al, 1983, Genain et al, 1983. Rosset and Vergrat (1971) have shown that in normal human subjects sodium restriction results in a decrease in plasma angiotensinogen and also an increase in PRA, while Chen et al (1983) have reported increased plasma angiotensinogen and significant elevation of the prohormone in some brain regions of rats deprived of water for 72h.…”
Section: Discussionmentioning
confidence: 99%
“…Since an endogenous brain renin-angiotensin system was proposed by Ganten et al (1971) and Fisher-Ferraro et al (1971), several investigations have been performed in order to clarify its contribution to blood pressure regulation and water-electrolyte balance under physiological and pathological conditions (Fuxe et al, 1976, Schelling et al, 1980. Several studies have tried to elucidate the relationship between the brain and the peripheral renin-angiotensin system by simultaneous measurements of plasma and cerebrospinal fluid (CSF) renin (Brosnihan et al, 1982), angiotensin II (Suzuki et al, 1983) and angiotensinogen (Finkielman et al, 1972, Ruiz et al, 1983, Schelling et al, 1983. Accumulated evidence from such studies has indicated that there may be a close relationship between these two compartments.…”
mentioning
confidence: 99%